Pelatihan PTK Bagi Guru Untuk Meningkatkan Kualitas Pembelajaran SDN Pai Kota Makassar - Abdul Wahid; Nur Afni; Nurhidayatullah Dahlan; Rahmah Kumullah; Abrina Maulidnawati Jumrah; Sri Hastati (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of the PKM program is to assist teachers at SDN Pai Makassar City in terms of proposals for classroom action research, implementation of classroom actions, and reporting of classroom action research results. The form of this training is by conducting training workshops. The location in this PKM is SDN Pai which is located on Jalan Perintis Kemerdekaan KM. 18 Biringkanaya District, Makassar City. The method used in this activity is classical and discussion which includes several stages, namely the delivery of proposal systematic material, material regarding the technical implementation of research, preparation of proposals, assistance for research implementation and preparation of final research reports. The results achieved in this activity are the increased understanding of teachers in classroom research including making proposals, technical implementation of research to reporting, and research which is expected to be used as an improvement in the learning process in class, recommendations for learning models.